Walking Clinic in ambulatory surgery – A patient based concept: A Portuguese pioneer project. (June 2015) - Vinagreiro, M.; Valverde, J.N.; Alves, D.; Costa, M.; Gouveia, P.; Guerreiro, E.
Abstract: Introduction: Walking Clinic is an innovative, efficient and easily reproducible concept adapted to ambulatory surgery. It consists of a preoperative single day work-up, with a surgeon, an anesthetist and a nurse. The aim of this study was to evaluate patient satisfaction and its determinants. Methods: A survey was applied to 171 patients (101 of the Walking Clinic group and 70 not engaged in this new concept). Patient satisfaction was assessed evaluating five major questionnaire items: secretariat (quality of the information and support given), physical space (overall comfort and cleanliness), nurses and medical staff (willingness and expertise), and patients (waiting time until pre-operative consults and exams, waiting time until being scheduled for surgery, surgery day waiting time and postoperative pain control). Furthermore, overall assessment of the received treatment, and probability of patient recommending or returning to our ambulatory unit were also analyzed. Results: Walking Clinic group had overall better results in the five major questionnaire items assessed, with statistical significance, except for the physical space. It also showed better results regarding the sub-items postoperative pain control, waiting time until being scheduled for surgery and surgery day waiting time. Discussion: The results confirm better patient satisfaction with this new concept. Conclusion: The Walking Clinic concept complements all the tenets of ambulatory surgery, in a more efficient manner. Highlights: "Walking Clinic" is a concept created for quality improvement in healthcare. "Walking Clinic" consists of a preoperative single day work-up. "Walking Clinic" patients had better postoperative pain control. Results confirmed better patient satisfaction with the "Walking Clinic" concept.